Multi-Objective H2/H∞ Gain-Scheduled Nuclear Core Control Design. Issue 1 (July 2017) - Lemazurier, L.; Yagoubi, M.; Chevrel, P.; Grossetête, A.
Abstract: The scope of this paper is advanced Nuclear Core control. First a Core kinetic nonlinear model is developed and calibrated by means of MANTA/SMART simulation codes. By linearization, a set of Linear Time Invariant (LTI) models are then obtained around some predetermined operating points depending on the nuclear core power level. Moreover, thanks to a new multi-objective H2 /H∞ ;, control approach, a set of fixed structure output feedback controllers are designed for appropriately chosen set of power levels. Furthermore, these controllers are interpolated to synthesize a gain-scheduled controller. Finally, simulations on the nonlinear Core model show appreciable performances which comply with the specified requirements.